Phenomenological Research Findings on Adult Learners’ Experiences with the Portfolio Process - Benjamin A. Jimenez (Adult Education Research Conference, 2015)
This study was conducted to identify the essence of the portfolio process, a form of prior learning assessment, as experienced and described by adult learners. The findings to be presented focus on the participants’ experiences with portfolios that provided them with a significant sense of validation. They described experiencing validation and an increase in the sense of worth of their prior learning, skills, and work in relation to their portfolio development.
Keywords: prior learning assessment (PLA); portfolio; tacit knowledge; validation